2019
DOI: 10.3389/fpsyt.2019.00743
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Opioid Dependence on Visuospatial Memory and Its Associations With Depression and Anxiety

Abstract: Introduction: The cognitive impact of opioid dependence is rarely measured systematically in everyday clinical practice even though both patients and clinicians accept that cognitive symptoms often occur in the opioid-dependent population. There are only a few publications which utilized computerized neuropsychological tests to assess possible impairments of visuospatial memory in opioid-dependent individuals either receiving opioid replacement therapy (ORT) or during subsequent short-term abstinence and the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…During the one-year follow-up period, 19 of the 37 patients undergoing MMT (51.35%) relapsed. The number of occurrences of relapse within a year was 5.25 ± 2.83 (range, [1][2][3][4][5][6][7][8][9][10][11]. The number of relapses was negatively related to the total methadone dose in 1 year (r = −0.515, p = 0.001, Bonferroni corrected p = 0.05/5 = 0.01; Figure 3).…”
Section: Relapsementioning
confidence: 97%
See 1 more Smart Citation
“…During the one-year follow-up period, 19 of the 37 patients undergoing MMT (51.35%) relapsed. The number of occurrences of relapse within a year was 5.25 ± 2.83 (range, [1][2][3][4][5][6][7][8][9][10][11]. The number of relapses was negatively related to the total methadone dose in 1 year (r = −0.515, p = 0.001, Bonferroni corrected p = 0.05/5 = 0.01; Figure 3).…”
Section: Relapsementioning
confidence: 97%
“…The preprocessing was performed using DPABI, 1 SPM12, 2 and MATLAB 8.1 3 for neuroimaging. The resting-state fMRI dates for each participant were corrected for slice timing to eliminate time differences caused by multi-slice interval imaging.…”
Section: Image Data Processing Preprocessingmentioning
confidence: 99%
“…The participants with a history of heroin abuse performed normally on the digit span task but demonstrated impaired verbal WM on the N-back task compared to HC. Additionally, Ersche et al (2006) and Tolomeo et al (2019) found visuospatial memory deficits in opioid-dependent participants, implicating a non-verbal WM impairment as well. These studies included the pattern recognition memory task from the Cambridge Neuropsychological Test Automated Battery (CANTAB) ( Fray et al, 1996 ), which involved participants viewing sets of geometric patterns and later choosing the pattern they recognized from a two-alternative forced choice test of the patterns.…”
Section: Introductionmentioning
confidence: 93%
“…One meta‐analysis of methadone‐maintained individuals reported neurocognitive deficits in working memory, attention, cognitive flexibility and other areas compared with controls [20]. In another study both methadone and buprenorphine users exhibited deficits in visuospatial working memory, which were strongly correlated with higher mood and anxiety symptom scores [21]. This highlights the potential need to pursue abstinence‐based therapy in OUD.…”
Section: Clinical Presentations and Underlying Mechanismsmentioning
confidence: 99%